A Biohybrid Material With Extracellular Matrix Core and Polymeric Coating as a Cell Honing Cardiovascular Tissue Substitute - Mudigonda, Jahnavi; Xu, Dongyang; Amedi, Alan; Lane, Brooks A.; Corporan, Daniella; Wang, Vivian; Padala, Muralidhar (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the feasibility of a hybrid material in which decellularized pericardial extracellular matrix is functionalized with polymeric nanofibers, as a cardiovascular tissue substitute. Background: A cardiovascular tissue substitute, which is gradually resorbed and is replaced by the host’s native tissue, has several advantages. Especially in children and young adults, a resorbable material can be useful in accommodating growth, but also enable rapid endothelialization that is necessary to avoid thrombotic complications. In this work, we report a hybrid material, wherein decellularized pericardial matrix is functionalized with a layer of polymeric nanofibers, to achieve the mechanical strength for implantation in the cardiovascular system, but also have enhanced cell honing capacity. Methods: Pericardial sacs were decellularized with sodium deoxycholate, and polycaprolactone-chitosan fibers were electrospun onto the matrix. Tissue-polymer interaction was evaluated using spectroscopic methods, and the mechanical properties of the individual components and the hybrid material were quantified. In vitro blood flow loop studies were conducted to assess hemocompatibility and cell culture methods used to assess biocompatibility. Results: Encapulsation of the decellularized matrix with 70µm thick nanofiber matrix of polycaprolactone-chitosan was feasible and reproducible. Spectroscopy of the cross-section depicted new amide bond formation and C–O–C stretch at the interface. An average peel strength of 56.13±11.87 mN/mm2 was measured, that is sufficient to withstand a high shear of 15 dynes/cm2 without delamination. Mechanical strength and extensibility ratio of the decellularized matrix alone was 18,000+4200 KPa, and 0.18+0.03 %, whereas that of the hybrid was higher at 20,000+6600 KPa, 0.35+0.20%. Anisotropy index and stiffness of the biohybrid were increased as well. Neither thrombus formation, nor platelet adhesion or hemolysis were measured in the in vitro blood flow loop studies. Cellular adhesion and survival were adequate in the material. Conclusion: Encapsulating a decellularized matrix with a polymeric nanofiber coating, has favorable attributes for use as a cardiovascular tissue substitute.